Uncanny rest : for antiphilosophy - Moreiras, Alberto (Duke University Press, 2022)
"In Uncanny Rest Alberto Moreiras offers a meditation on intellectual life under the suspension of time and conditions of isolation. Focusing on his personal day to day experiences of the "shelter-in-place" period during the first months of the coronavirus pandemic, Moreiras engages with the limits and possibilities of critical thought in the realm of the infrapolitical-the conditions of existence that exceed average understandings of politics and philosophy. In each dated entry he works through the process of formulating a life's worth of thought and writing while attempting to locate the nature of thought once the coordinates of everyday life have changed. Offering nothing less than a phenomenology of thinking, Moreiras shows how thought happens in and out of a life, at a certain crossroads where memories collide, where conversations with interlocutors both living and dead evolve, and thinking during a suspended state becomes provisional and uncertain."--